Early transjugular intrahepatic portosystemic shunt in cirrhotic patients with acute variceal bleeding. Issue 9 (September 2015) - Deltenre, Pierre; Trépo, Eric; Rudler, Marika; Monescillo, Alberto; Fraga, Montserrat; Denys, Alban; Doerig, Christopher; Fournier, Nicolas; Moreno, Christophe; Moradpour, Darius; Bureau, Christophe; Thabut, Dominique
<x xml:space="preserve">Abstract</x> Introduction There is conflicting evidence on the benefit of early transjugular intrahepatic portosystemic shunt (TIPSS) on the survival of patients with acute variceal bleeding (AVB). Aim To assess the effect of early TIPSS on patient prognosis. Materials and methods We carried out a meta-analysis of trials evaluating early TIPSS in cirrhotic patients with AVB. Results Four studies were included. Early TIPSS was associated with fewer deaths [odds ratio (OR)=0.38, 95% confidence interval (CI)=0.17–0.83, P=0.02], with moderate heterogeneity between studies (P=0.15, I2=44%). Early TIPSS was not significantly associated with fewer deaths among Child–Pugh B patients (OR=0.35, 95% CI=0.10–1.17, P=0.087) nor among Child–Pugh C patients (OR=0.34, 95% CI=0.10–1.11, P=0.074). There was no heterogeneity between studies in the Child–Pugh B analysis (P=0.6, I2=0%), but there was a high heterogeneity in the Child–Pugh C analysis (P=0.06, I2=60%). Early TIPSS was associated with lower rates of bleeding within 1 year (OR=0.08, 95% CI=0.04–0.17, P<0.001) both among Child–Pugh B patients, (OR=0.15, 95% CI=0.05–0.47, P=0.001) and among Child–Pugh C patients (OR=0.05, 95% CI=0.02–0.15, P<0.001), with no heterogeneity between studies. Early TIPSS was not associated with higher rates of encephalopathy (OR=0.84, 95% CI=0.50–1.42, P=0.5). Conclusion Cirrhotic patients with AVB treated with early TIPSS had lower death rates and lower rates of clinically significant bleeding within 1 year compared with patients treated without early TIPSS. Additional studies are required to identify the potential risk factors leading to a poor prognosis after early TIPSS in patients with AVB and to determine the impact of the degree of liver failure on the patient's prognosis.